2013
DOI: 10.1038/cddis.2013.201
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in c-Myc phenotypes resulting from dynamin-related protein 1 (Drp1)-mediated mitochondrial fission

Abstract: The c-Myc (Myc) oncoprotein regulates numerous phenotypes pertaining to cell mass, survival and metabolism. Glycolysis, oxidative phosphorylation (OXPHOS) and mitochondrial biogenesis are positively controlled by Myc, with myc−/− rat fibroblasts displaying atrophic mitochondria, structural and functional defects in electron transport chain (ETC) components, compromised OXPHOS and ATP depletion. However, while Myc influences mitochondrial structure and function, it is not clear to what extent the reverse is tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Abundant experimental evidence suggests that downregulation of mitochondrial respiration capacity is intimately linked to the process of malignant transformation (43)(44)(45)(46). Indeed, we found that the process of transforming BJ fibroblast cells led to the reduction of RC and RR, providing direct evidence connecting malignant transformation to changes in respiratory properties, and increased vulnerability to antimitochondria agents such as metformin.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Abundant experimental evidence suggests that downregulation of mitochondrial respiration capacity is intimately linked to the process of malignant transformation (43)(44)(45)(46). Indeed, we found that the process of transforming BJ fibroblast cells led to the reduction of RC and RR, providing direct evidence connecting malignant transformation to changes in respiratory properties, and increased vulnerability to antimitochondria agents such as metformin.…”
Section: Discussionsupporting
confidence: 55%
“…Knowledge has been growing steadily about metabolic differences between cancer cells and benign cells. Although the molecular mechanisms for the metabolic adaptation are multifaceted and likely variable in different cancer cells, several common tumor suppressors or oncogenes, such as p53 and RAS, have been linked to the regulation of glycolysis and mitochondrial activity (43)(44)(45)(46). We postulated that cancer cells have lower RC/RC than their normal counterparts as a direct consequence of the transformation process.…”
Section: Malignant Transformation Reduces Rc and Rr And Increases Celmentioning
confidence: 99%
“…Mitochondria were visualized with mouse anti-ATP Synthase (ThermoFisher, Clone 4.3E8.D10), peroxisomes with rabbit anti-PMP70 (Abcam), and nuclei with Hoechst Dye (Sigma), using standard techniques as described [22, 23]. Secondary antibodies used were goat anti-mouse Cy3 (Jackson Immunolaboratories) and goat anti-rabbit Alexa 488 (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…S1F). This may reflect a compensatory change by which cells conserve energy through the reduction of biomass (see below) (17).…”
Section: Inactivation Of Pdha1 Reduces Cell Size But Not Growth Ratementioning
confidence: 99%